Fish Farmer Producer Organizations - Can it become a game changer? - De, Himansu Kumar; Saha, Gour Sundar; Mahapatra, A. S.; Sreenivasulu, G. (Journal of the Inland Fisheries Society of India, 2022)
Towards the end of the 19th century, farmers’ cooperatives were viewed as an attractive mechanism to deal with increasing problems of rural indebtedness and exploitation, for solving common problems relating to credit, supplies of inputs and marketing of agricultural produce that led to implementation of the Cooperative Society Act (Deepa et al., 2018). The concept of producer companies was initiated by the Indian government in 2002 as a part of ongoing agro-food transformations in the country with the first producer company registered in 2012 (Trebbin, 2014). A Producer Organization (PO) is a legal entity formed by primary producers such as farmers, milk producers, fishermen, weavers, rural artisans, craftsmen, etc. (NABARD, 2015). The Farmer Producer Companies (FPCs) are fundamentally farmer-owned and farmer- governed micro-enterprises which can be considered as hybrids between cooperative societies and private companies (Mukherjee et al., 2018). Producer companies are a promising tool to strengthen farmers’ position in their relationship with supermarket chains in India, but one which needs further improvement (Trebbin, 2014).